Lord I'm Coming Home : Everyday Aesthetics in Tidewater North Carolina - Forrest, John; Blincoe, Deborah (Ithaca, NY : Cornell University Press, 2018)
Lord I'm Coming Home focuses on a small, white, rural fishing community on the southern reaches of the Great Dismal Swamp in North Carolina. By menas of a new kind of anthropological fieldwork, John Forrest seeks to document the entire aesthetic experience of a group of people, showing the aesthetic to be an "everyday experience and not some rarefied and pure behavior reserved for an artistic elite."The opening chapter of the book is a vivid fictional narrative of a typical day in "Tidewater," presented from the perspective of one fisherman. In the following two chapters the author sets forth the philosophical and anthropological foundations of his book, paying particular attention to problems of defining "aesthetic," to methodolgocial concerns, and to the natural landscape of his field site. Reviewing his own experience as both participant and observer, he then describes in scrupulous detail the aesthetic forms in four areas of Tidewater life: home, work, church, and leisure. People use these forms, Forrest shows, to establish personal and group identities, facilitate certain kinds of interactions while inhibiting others, and cue appropriate behavior. His concluding chapter deals with the different life cycles of men and women, insider-outsider relations, secular and sacred domains, the image and metaphor of "home," and the essential role that aesthetics plays in these spheres. The first ethnography to evoke the full aesthetic life of a community, Lord I'm Coming Home will be important reading not only for anthropologists but also for scholars and students in the fields of American studies, art, folklore, and sociology.
Frontmatter -- Contents -- Preface -- 1. The Fishing Day -- 2. The Aesthetic Realm -- 3. The Field Site -- 4. Aesthetics at Home -- 5. Aesthetics at Work -- 6. Aesthetics of the Church -- 7. Aesthetics of Leisure -- 8. Synthesis -- Appendix A: Outlines of Selected Sermons -- Appendix B: Tale of Wallace Tyler, Version #2 -- References -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Jun 2022)
Keywords: Aesthetics -- Social aspects -- North Carolina; Ethnology -- North Carolina; Anthropology; 2 -- isacsh